High competence MIMO-OFDM with generalized led index modulation - Showme, N; Ramachandran, Anush; Sekhar, Nihal; Shankar, Ravi (International Journal of Engineering and Technology, 2018)
Optical communication in specific the visible light communication (VLC) is the next generation technology in the field of data transmission. This paper proposes an idea of improving the transmission rate of the data via a totally different method of channel using optical light communication. Here, the normal radio frequency waves arenâ€™t being used at all. Simple light will give us the required channel medium to send the data over a range. The system that is being proposed separates each data signal and sends it one by one to the light emitting modulation. The real and imaginary part of the complex time domain OFDM signals are taken apart and are sent over a frequency-flat light channel. As a standard it was demonstrated that the performance of the simulation in two different configurations with various numbers of transmitting and receiving antennas.Â Â